Interpersonal Communication between Children and Parents: A Study of Gender, Education, and Region Dimensions and Its Contribution to Guidance and Counseling - Risdawati Siregar; Yuni Sarah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to describe interpersonal communication between children and parents in terms of gender, parental education level, and residential area, and to test the differences. The research method used ex post facto with a 2 x 3 x 2 factorial design. The study population consisted of adolescents in Batu Nadua District, Padangsidimpuan City, with a sample of 263 people selected through a combination of cluster random sampling and proportional random sampling. The research instrument was a Likert scale, while data analysis used descriptive statistics and ANOVA. The research findings show that interpersonal communication between children and parents is generally in the good category. Furthermore, there are differences in interpersonal communication between children and parents in terms of gender, where girls score higher than boys. At the same time, there are no differences in terms of parental education level and residential area. These findings have implications for the importance of guidance and counseling service programs, especially in family guidance. Keywords: interpersonal communication, children and parents, guidance and counseling